SmartFFR, a New Functional Index of Coronary Stenosis: Comparison With Invasive FFR Data - Siogkas, Panagiotis K.; Lakkas, Lampros; Sakellarios, Antonis I.; Rigas, George; Kyriakidis, Savvas; Stefanou, Kostas A.; Anagnostopoulos, Constantinos D.; Clemente, Alberto; Rocchiccioli, Silvia; Pelosi, Gualtiero; Parodi, Oberdan; Papafaklis, Michail I.; et al. (Frontiers in Cardiovascular Medicine, 2021)
Aims In this study, we evaluate the efficacy of SmartFFR, a new functional index of coronary stenosis severity compared with gold standard invasive measurement of fractional flow reserve (FFR). We also assess the influence of the type of simulation employed on smartFFR (i.e. Fluid Structure Interaction vs. rigid wall assumption). Methods and Results In a dataset of 167 patients undergoing either computed tomography coronary angiography (CTCA) and invasive coronary angiography or only invasive coronary angiography (ICA), as well as invasive FFR measurement, SmartFFR was computed after the 3D reconstruction of the vessels of interest and the subsequent blood flow simulations. 202 vessels were analyzed with a mean total computational time of seven minutes. SmartFFR was used to process all models reconstructed by either method. The mean FFR value of the examined dataset was 0.846±0.089 with 95% CI for the mean of 0.833-0.858, whereas the mean SmartFFR value was 0.853±0.095 with 95% CI for the mean of 0.84-0.866. SmartFFR was significantly correlated with invasive FFR values (RCCTA=0.86, pCCTA<0.0001, RICA=0.84, pICA<0.0001, Roverall=0.833, poverall<0.0001), showing good agreement as depicted by the Bland-Altman method of analysis. The optimal SmartFFR threshold to diagnose ischemia was ≤0.83 for the overall dataset, ≤0.83 for the CTCA-derived dataset and ≤0.81 for the ICA-derived dataset, as defined by a ROC analysis (AUCoverall=0.956, p<0.001, AUCICA=0.975, p<0.001, AUCCCTA=0.952, p<0.001). Conclusion SmartFFR is a fast and accurate on-site index of hemodynamic significance of coronary stenosis both at single coronary segment and at two or more branches level simultaneously, which can be applied to all CTCA or ICA sequences of acceptable quality.